Antimicrobial Susceptibility Pattern of Pathogenic Bacteria Causing Urinary Tract Infections at Azadi Hospital In Duhok City\Kurdistan Region of Iraq - Abdulrahman, Ibtesam S. (Science Journal of University of Zakho, 2018)
Urinary tract infections represents one of the most common diseases encountered in medical practice affecting people of all ages from the neonate to the geriatric age group. The aim of this study was to determine and evaluate the antimicrobial susceptibility patterns for most common strains of bacterial urine isolates taken from patients at Azadi teaching hospital laboratories in Duhok city/Kurdistan region in Iraq, for two years (2014 and 2015). A retrospective survey study was conducted and 1003 data of urine culture sensitivity test were collected from recorded archives of the Azadi hospital of two years; 2014 and 2015. The study included all recorded positive urine samples cultures isolated from inpatients and outpatients. Results revealed that the female to male ratio for urinary tract infection was 2.7:1 and the most common microorganisms isolated were Escherichia coli (52%), Staphylococcus aureus (11%), Staphylococcus haemolyticus (9.6%) and Klebsiella pneumoniae (8.1%). In general maximum sensitivity was seen for Meropenem (94.9%), followed by Imipenem (89.7%) and Ertapenem (88.7%). The maximum resistance was seen against Cefazolin (79.7%) and Amoxicillin/clavulanic acid (77.5%). The antibiotic sensitivity pattern of E. coli reveals that the maximum sensitivity was seen for Meropenem (97.3%) and Imipenem (95.6%). The maximum resistance was seen against Amoxicillin/clavlanic acid (83.1%). The resistance against many commonly used antibiotics have been increased which limit the options for treating urinary tract infection. This is resulted from uncontrolled use of the antibiotics and lack of policies and guidelines for their use in public health.